ON SMALL TANGENTIAL MASS FORCES THAT MAY EXIST IN THE LITHOSPHERE. THEIR ROLE IN TECTONICS AND GEODYNAMICS - Yu. L. Rebetsky (Геодинамика и тектонофизика, 2016)
The author continues to investigate additional planetary-level stresses that occur in the crust due to distributed tangential mass forces. Such forces may be related to the daily rotation of the Earth and movements of the relatively solid core relative to the geocenter. In [Rebetskii, 2016], he discusses how the tangential mass forces in the continental crust are influencing additional meridional and latitudinal stresses and attempted to explain regularities of planetary fracturing. In this paper, he considers the role of the tangential mass forces in the occurrence of lateral movement of the lithospheric plates.The author proposes to estimate amplitudes of the tangential mass forces from the difference between the two global ellipsoids of rotation. The reference ellipsoid averages the level surface of the gravity potential, and the second ellipsoid averages the physical surface of the Earth, separately considering continents and oceans. The Earth’s dynamic compression factor estimated from satellite data is 1/305.5. This value corresponds well to the average polar compression of the two rotation ellipsoids, which approximately describes the shape of the Earth’s physical surface. Thus, in the first approximation, the polar compression of the Earth’s physical surface is less than that of the reference ellipsoid (1/298.25) that approximately describes the shape of the level surface of gravity (i.e. geoid).Gravity vectors deviate from the normal to the physical surface of the Earth by relatively small angles, according to calculations from the data on rotation ellipsoids (a maximum value of 16.4 at the 45° latitude). Tangential mass forces are thus small (2.15×10–4 G/cm3 at the 45° latitude). Due to small tangential forces, shear stresses about 0.3 MPa may occur at the base of the continental lithosphere (depths of 120–150 km). In their turn, such stresses can cause a shear flow in the asthenosphere, which provides for movements of the lithospheric plates at velocities of a few centimeters per year. The estimates in this study suggest that the tangential mass forces can be viewed as a possible source of the movements of the lithospheric plates.Regional rotation ellipsoids, that average the physical surface of the continental and oceanic parts of the Earth, were estimated separately for the northern and southern hemispheres. The largest deviations of the ellipsoids from the reference ellipsoid were revealed for the oceanic parts of both hemispheres of the Earth. The regional ellipsoids for the oceanic parts show smaller polar compression (1/313.1 in the northern hemisphere, and 1/306.9 in the southern hemisphere) than that of the reference ellipsoid, and this predetermines the north-south orientation of the tangential mass forces from the poles to the equator. Compared to the reference ellipsoid, polar compression values estimated for the regional ellipsoids of the continental crust are larger (1/296.2) in the northern hemisphere and smaller (1/303.2) in the southern hemisphere. According to the calculations, the oceanic lithosphere makes the major contribution to submeridional movements of the continental plates.